2020
DOI: 10.3389/fonc.2020.01471
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Prognostic Stage of American Joint Committee on Cancer Eighth Edition Staging Manual in Invasive Lobular Carcinoma Compared to Invasive Ductal Carcinoma and Proposal of a Novel Score System

Abstract: The objective of this study was to evaluate the American Joint Committee on Cancer (AJCC) pathological prognostic stage among patients with invasive ductal carcinoma (IDC) and invasive lobular carcinoma (ILC) and to propose a modified score system if necessary. Methods: Women diagnosed with IDC and ILC during 2010-2015 in the Surveillance, Epidemiology, and End Results (SEER) database were retrospectively identified. Disease-specific survival (DSS) and overall survival (OS) were estimated by Kaplan-Meier metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The prognosis of ILC was similar to that of IDC in general, and a histologically high-risk subset of ILC based on the Ki-67 and/or histological grade, and ER status was reported previously [16,17]. We did not perform this type of grading for ILC because, currently, a diagnosis of ILC is almost selectively given for classical type ILC alone in Japan, and is usually classified as NG1.…”
Section: Discussionsupporting
confidence: 65%
“…The prognosis of ILC was similar to that of IDC in general, and a histologically high-risk subset of ILC based on the Ki-67 and/or histological grade, and ER status was reported previously [16,17]. We did not perform this type of grading for ILC because, currently, a diagnosis of ILC is almost selectively given for classical type ILC alone in Japan, and is usually classified as NG1.…”
Section: Discussionsupporting
confidence: 65%
“…According to the results of clinical data analysis of BC tissues in the TCGA, the expression level of ZNF775 in patients with ILC was signi cantly higher than that of IDC. At present, the most common histological types of BC are IDC and ILC among which IDC accounts for 70%-75%, and ILC accounts for about 10% of all cases [45] . One study found that among 16,703 patients with metastatic BC in the ESME database, patients with ILC had poorer overall survival and PFS1 compared to patients with IDC [45] .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most common histological types of BC are IDC and ILC among which IDC accounts for 70%-75%, and ILC accounts for about 10% of all cases [45] . One study found that among 16,703 patients with metastatic BC in the ESME database, patients with ILC had poorer overall survival and PFS1 compared to patients with IDC [45] .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Therefore, the 8th edition AJCC staging system incorporated the prognostic biomarkers ER, PR, HER2 and HG, and multigene assays when available to form the prognostic staging system (PS). Since the publication of the 8th edition AJCC staging system, the PS has repeatedly been validated and proved superior to the AS in Western [6][7][8][9] and Asian populations. 10,11 Nevertheless, the prognostic value of PS for breast cancer based on molecular subtype has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 8th edition AJCC PS manual has been published for more than three years, most studieds have validated its superiority over AS. [6][7][8][9][10][11] To the best of our knowledge, only a few studies have investigated the value of PS in different molecular subtypes. In a retrospective study of 170 HER2-enriched breast cancers, Zhou et al found that both AS and PS had prognostic value in this subtype of breast cancer.…”
mentioning
confidence: 99%